Poor Positive Accuracy of QuickVue Rapid Antigen Tests during the Influenza A (H1N1) 2009 Pandemic - Stevenson, Heather L. (American Society for Microbiology (ASM), 2010)
We assessed the accuracy of positive QuickVue rapid influenza virus antigen test results. Using reverse transcription (RT)-PCR as the gold standard, 17 (37.8%) of 45 QuickVue-positive specimens were determined to be false positives. We report an unexpectedly high rate of false-positive QuickVue results during a period of high influenza A (H1N1) 2009 virus prevalence.